2022
DOI: 10.37934/cfdl.14.12.111125
|View full text |Cite
|
Sign up to set email alerts
|

Flow of Casson Nanofluid Past a Permeable Surface: Effects of Brownian Motion, Thermophoretic Diffusion and Lorenz force

Abstract: This study is aimed at testing the significance of Brownian movement and thermophoresis dispersion on MHD Casson nano liquid limit layer stream past a nonlinear slanted permeable extending surface, with the impact of convective limits and warm radiation with a synthetic response. Nonlinear ODEs are gotten from overseeing nonlinear PDEs by utilizing good comparability changes. The amounts related to building angles, for example, skin grating, Nusselt and Sherwood numbers alongside different effects of factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In this section, the successive outcomes for physical variables are evaluated by using the values chosen in the references [2,4,9,13] as; 𝑀 = 1.0, 𝛽 = 0.1, 𝛾 = 0.1, π‘ƒπ‘Ÿ = 2.0, 𝐿𝑒 = 2.0, 𝑁𝑏 = 0.1, 𝑆 = 0.1, 𝑁𝑑 = 0.1, 𝑅 = 0.1, πΎπ‘Ÿ = 0.1, 𝑄 = 0.0, 𝐸 = 0.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the successive outcomes for physical variables are evaluated by using the values chosen in the references [2,4,9,13] as; 𝑀 = 1.0, 𝛽 = 0.1, 𝛾 = 0.1, π‘ƒπ‘Ÿ = 2.0, 𝐿𝑒 = 2.0, 𝑁𝑏 = 0.1, 𝑆 = 0.1, 𝑁𝑑 = 0.1, 𝑅 = 0.1, πΎπ‘Ÿ = 0.1, 𝑄 = 0.0, 𝐸 = 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…If the applied yield stress is larger than the applied shear stress, the applied material behaves as a solid; otherwise, it behaves as a liquid and begins to move. Raju et al, [1][2][3] and Vyakaranam et al, [4] have discussed the Casson fluid application. The magnetohydrodynamic Carreau and Casson fluids' exponential heat source/sink, momentum, and thermal transport over the spinning paraboloid have all been examined by Kumaran et al, [5].…”
Section: Introductionmentioning
confidence: 99%
“…Dharmaiah et al, [27] has analysed the numerical analysis of heat and mass transfer with viscous dissipation, Joule dissipation, and activation energy. Kumar et al, [28] was studied the perturbation methodology for electromagnetic radiative fluxing of chemical reactive Casson fluid flow under heat source (sink) effectiveness Many researchers studied the effects of Cattaneo-Christov heat flux on chemically reacting nanofluids flow past a stretching sheet with joule heating effect and Soret-Dufour mechanisms on unsteady boundary layer flow of tangent hyperbolic flows [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Oke [43] proposed a modified Eyring Powell fluid and identified that the fluid can exhibit both shear thickening and shear thinning properties. Vaidya et al, [44] investigated the flow of reactive peristaltic nanofluid through an inclined channel under the influence of non-constant thermal conductivity and Vyakaranam [45] examined the Casson-based nanofluid in a permeable surface. A further study was carried out by Tan Jian et al, [46] to unravel the self-diffusion of nanoparticles by using dissipative particle dynamics.…”
Section: Introductionmentioning
confidence: 99%